2015
DOI: 10.1021/acs.jmedchem.5b00783
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lipoylation of the Immunodominant Epitope of Pyruvate Dehydrogenase Complex: Toward a Peptide-Based Diagnostic Assay for Primary Biliary Cirrhosis

Abstract: Primary biliary cirrhosis is an immune-mediated chronic liver disease whose diagnosis relies on the detection of serum antimitochondrial antibodies directed against a complex set of proteins, among which pyruvate dehydrogenase complex is considered the main autoantigen. We studied the immunological role of the lipoyl domain of this protein using synthetic lipoylated peptides, showing that the lipoyl chain chirality does not affect autoantibody recognition and, most importantly, confirming that both lipoylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…(D) The relationship between FDX1 and receptor genes expression in glioma. Frontiers in Medicine 11 frontiersin.org key genes by bioinformatics analysis, comparing the co-expression gene of FDX1 in gliomas with with an additional 6 lipoacylation-related genes (79)(80)(81)(82). The key genes were subjected to intersection analysis and expression correlation analysis, to screen and identify potential Cuproptosis process genes through co-expression network research methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(D) The relationship between FDX1 and receptor genes expression in glioma. Frontiers in Medicine 11 frontiersin.org key genes by bioinformatics analysis, comparing the co-expression gene of FDX1 in gliomas with with an additional 6 lipoacylation-related genes (79)(80)(81)(82). The key genes were subjected to intersection analysis and expression correlation analysis, to screen and identify potential Cuproptosis process genes through co-expression network research methods.…”
Section: Discussionmentioning
confidence: 99%
“…Recent blockbuster reports have found that FDX1, a key regulator of Cuproposis, regulates cell death by influencing fatty protein lipoylation. To further explore the role of FDX1 in gliomas, we attempted to identify potential Cuproptosis key genes by bioinformatics analysis, comparing the co-expression gene of FDX1 in gliomas with with an additional 6 lipoacylation-related genes ( 79 82 ). The key genes were subjected to intersection analysis and expression correlation analysis, to screen and identify potential Cuproptosis process genes through co-expression network research methods.…”
Section: Discussionmentioning
confidence: 99%
“…Sera from 27 TD1 and 29 NBD subjects were tested by SP-ELISA using the synthetic peptides 1 and 2. The applied ELISA protocol for detection of IgM and IgG antibodies against [(deoxyFru)Lys 173 ]PDC-E2(167-186)-KKKK and [(deoxyFru)Lys 7 ]CSF114 antigens was previously developed and applied routinely in our laboratory for [Lys 173 ]PDC-E2(167-186)-KKKK and [Lys 7 ] CSF114 antigens (Lolli et al 2005a;Pacini et al 2015;Nuti et al 2018). The obtained IgM and IgG data distribution is reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously proposed to use peptides as synthetic antigens for efficient detection, including the aforementioned chemical modifications in the strategic positions in selected sequences. In particular, we employed CSF114 as an optimally designed β-turn conformation, and the PDC-E2(167-186) fragment, which is a mitochondrial protein component of the pyruvate dehydrogenase complex (Lolli et al 2005b;Pacini et al 2015;Nuti et al 2018).…”
Section: Table 3 Clinical Characteristics Of the Subjects Under Studymentioning
confidence: 99%
See 1 more Smart Citation